THE HEGEMONY OF ENGLISH IN INDONESIAN MOVIES TITLES 2016 - Reza Jonesa; Jufrizal Jufrizal; Delvi Wahyuni (English Language and Literature, 2018)
This research aimed at identifying the language that dominantly used rather than other languages in Indonesian movies titles 2016. Clearly, it intended to see the used of English, the forms of language hegemony of English and the tendency of title characteristics in Indonesian movies titles 2016. The method used in this research was descriptive. The data of this research were the words, phrases or clauses as the titles of Indonesian movies in 2016. In other word, the research data consisted of 131 titles. From the 131 titles, it was found 80 data of forms of langauge hegemony of English. Based on the research finding, the dominant language used in Indonesian movies titles 2016 is Indonesian language that was about 76 titles (58%). Moreover, it also showed that there were four forms of language hegemony of English found in Indonesian movies titles 2016. It also can be an evidence of the existence of language hegemony of English in Indonesian movies titles. The four forms were code switching, code mixing, borrowing word and language interference. Meanwhile, the most frequent characteristics of the Indonesian movies titles were concise and accurate which means that Indonesian movies titles 2016 contained the story of the movies obviously.